Efetividade de protocolos para redução de permanência de sonda vesical de demora gerenciados por enfermeiros: Revisão integrativa - Miranda, Maria Estela de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Objective: to analyze the levels of evidence from research published in the form of articles, whose object of study followed the evaluation of protocols managed by nurses to reduce the length of indwelling urinary catheter (IUC) and urinary tract infection (UTI), in hospitalized adult and elderly patients. Method: an integrative literature review, based on the research question: What is the effectiveness of protocols managed by nurses for the removal of indwelling urinary catheters from adults and elderly hospitalized with UTI incidence? The sample was selected by accessing the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), MEDLINE Complete - EBSCO, Scopus, Current Nursing and Allied Health Literature (CINAHL) and Web of Science (WoS), without determining a specific search field (article title; abstract; keywords), but choosing “all fields”. The search strategy used was controlled descriptors combined with Boolean operators, arranged in the Medical Subject Headings (MeSH). In the LILACS database, the Health Sciences Descriptors (DeSC) were used. The inclusion criteria were: complete articles with abstracts and related to the research object, in Portuguese, English and Spanish, published in national and international journals, indexed in the aforementioned databases, from 01/01/2015 to 26/04/2021. Results: of the 60 articles surveyed, three observational studies met the criteria, being two cohort studies and a case-control study, considered with evidence levels of “4”. All from the evaluation of protocols in ICUs of hospitals in the United States of America, which demonstrated effectiveness in reducing UTIs caused by IUC. The protocols are organized into tables, according to the variables used for data extraction: authors' surnames, year, journal, country and setting where the study took place, article language, objectives, protocol, main results/outcomes and conclusions of the research. Discussion: the synthesis of items contained in the three protocols was organized in six phases. These support IUC care for: decision making for its insertion, indications and contraindications for the continuous use of the catheter, insertion, maintenance, removal and after removal. It was found that although the protocols are relatively recent, they require revision, specifically for perineal care with a 2% chlorhexidine solution, twice a day, in female patients with IUC. Furthermore, it signals the need for nurses to be prepared, since graduation, to use the ultrasound device so that the professional can use it xi at the bedside, to estimate the residual value of urine, after the removal of the patient's IUC. Conclusions: the analyzed studies produced evidence, through studies of the effectiveness of protocols managed by nurses to reduce the length of stay of IUC and UTI, in hospitalized adults and elderly patients. Due to the benefits of protocols and the national scarcity of this type of research, the results of this review may support the design of new studies for protocol evaluations, in Brazilian institutions, through clinical trials

RESUMO Objetivo: analisar os níveis de evidências de pesquisas publicadas na forma de artigos, cujo objeto de estudo ateve-se à avaliação de protocolos geridos por enfermeiros para redução de permanência de sonda vesical de demora (SVD) e de infecção do trato urinário (ITU), em pacientes adultos e idosos hospitalizados. Método: revisão integrativa da literatura, a partir da questão de pesquisa: Qual a efetividade de protocolos gerenciados por enfermeiros, para remoção de sonda vesical de demora de adultos e idosos hospitalizados na incidência de ITU? A seleção da amostra deu-se por acesso às bases de dados: Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), MEDLINE Complete - EBSCO, Scopus, Current Nursing and Allied Health Literature (CINAHL) e Web of Science (WoS), sem determinar um campo específico de busca (article title; abstract; keywords), mas optando por “all fields”. Utilizou-se como estratégia de busca os descritores controlados combinados com operadores booleanos, dispostos no Medical Subject Headings (MeSH). Na base de dados LILACS empregou-se os Descritores em Ciências da Saúde (DeSC). Adotou-se como critérios de inclusão: artigos completos com resumos e relacionados ao objeto de pesquisa, nos idiomas português, inglês e espanhol, publicados em periódicos nacionais e internacionais, indexados nas bases de dados referidas, no período de 01/01/2015 a 26/04/2021. Resultados: dos 60 artigos levantados, três estudos observacionais preencheram os critérios, sendo dois estudos de coorte e um estudo caso controle, considerados com níveis de evidência “4”. Todos oriundos de avaliação de protocolos em Unidades de Terapia Intensiva de hospitais dos Estados Unidos da América, os quais demonstraram efetividade na redução das ITUs por SVD. Os protocolos encontram-se organizados em quadros, conforme variáveis utilizadas para extração dos dados: sobrenome dos autores, ano, periódico, país e cenário onde ocorreu o estudo, idioma do artigo, objetivos, protocolo, principais resultados/desfechos e conclusões das pesquisas. Discussão: organizou-se a síntese dos itens contidos nos três protocolos, em seis fases. Essas fundamentam os cuidados com a SVD para: tomada de decisão para sua inserção, indicações e contraindicações para o uso contínuo do cateter, inserção, manutenção, remoção e após a remoção. Verificou-se que apesar dos protocolos serem relativamenente recentes, demandam revisão, especificamente para o cuidado perineal com solução de clorexidina 2%, duas vezes ix ao dia, de pacientes do sexo feminino com SVD. Ademais, sinaliza a necessidade do enfermeiro ser preparado, desde a graduação, para utilizar o aparelho de ultrassom para que o profissional possa utilizá-lo à beira do leito, para estimar o valor residual de urina, após a retirada da SVD do paciente. Conclusões: as pesquisas analisadas produziram evidências, por meio de estudos de efetividade de protocolos geridos por enfermeiros para redução de permanência de SVD e de ITU, em pacientes adultos e idosos hospitalizados. Mediante os benefícios dos protocolos e a escassez nacional desse tipo de pesquisa, os resultados dessa revisão poderão subsidiar o delineamento de novos estudos para avaliações de protocolos, em instituições brasileiras, por meio de ensaios clínicos.
Effectiveness of nurse-managed protocols to reduce the length of indwelling catheters: Integrative review
Keywords: Catheters; Indwelling; Protocols; Nurses; Device removal; Urinary catheterization; Catheter-related infections; Urinary tract infections; Cateterismo urinário; Infecções relacionadas a cateter; Cateteres de demora; Protocolos; Infecções urinárias; Enfermeira e enfermeiros; Remoção de dispositivo